Multicenter standardization of phase-resolved functional lung MRI in patients with suspected chronic thromboembolic pulmonary hypertension - Moher Alsady, Tawfik; Voskrebenzev, Andreas; Behrendt, Lea; Olsson, Karen Maria; Heußel, Claus Peter; Grünig, Ekkehard; Gall, Henning; Ghofrani, Ardeschir; Roller, Fritz; Harth, Sebastian; Marshall, Helen; Hughes, Paul J. C.; et al. (Journal of magnetic resonance imaging, 2024)
BACKGROUND: Detection of pulmonary perfusion defects is the recommended approach for diagnosing chronic thromboembolic pulmonary hypertension (CTEPH). This is currently achieved in a clinical setting using scintigraphy. Phase-resolved functional lung (PREFUL) magnetic resonance imaging (MRI) is an alternative technique for evaluating regional ventilation and perfusion without the use of ionizing radiation or contrast media. - PURPOSE: To assess the feasibility and image quality of PREFUL-MRI in a multicenter setting in suspected CTEPH. - STUDY TYPE: This is a prospective cohort sub-study. - POPULATION: Forty-five patients (64 ± 16 years old) with suspected CTEPH from nine study centers. - FIELD STRENGTH/SEQUENCE: 1.5 T and 3 T/2D spoiled gradient echo/bSSFP/T2 HASTE/3D MR angiography (TWIST). - ASSESSMENT: Lung signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were compared between study centers with different MRI machines. The contrast between normally and poorly perfused lung areas was examined on PREFUL images. The perfusion defect percentage calculated using PREFUL-MRI (QDPPREFUL) was compared to QDP from the established dynamic contrast-enhanced MRI technique (QDPDCE). Furthermore, QDPPREFUL was compared between a patient subgroup with confirmed CTEPH or chronic thromboembolic disease (CTED) to other clinical subgroups. - STATISTICAL TESTS: t-Test, one-way analysis of variance (ANOVA), Pearson's correlation. Significance level was 5%. - RESULTS: Significant differences in lung SNR and CNR were present between study centers. However, PREFUL perfusion images showed a significant contrast between normally and poorly perfused lung areas (mean delta of normalized perfusion -4.2% SD 3.3) with no differences between study sites (ANOVA: P = 0.065). QDPPREFUL was significantly correlated with QDPDCE (r = 0.66), and was significantly higher in 18 patients with confirmed CTEPH or CTED (57.9 ± 12.2%) compared to subgroups with other causes of PH or with excluded PH (in total 27 patients with mean ± SD QDPPREFUL = 33.9 ± 17.2%). - DATA CONCLUSION: PREFUL-MRI could be considered as a non-invasive method for imaging regional lung perfusion in multicenter studies. - LEVEL OF EVIDENCE: 3 TECHNICAL EFFICACY: Stage 1.